Perancangan Alat Centrifuge Balance Berbasis Arduino Nano Untuk Mengetahui berat Kedua Sampel Darah Sudah Seimbang - Ramadhani Ariya Saputra; Andi Kurniawan Nugroho; Bayu Wahyudi (Jurnal Teknik dan Science, 2025)
A balance centrifuge is a tool to weigh two different samples to determine the balance of the two samples before proceeding to the centrifugation process. The electronic circuit consists of 2 Load Cells and other supporting components, which aim to measure and process heavy data from both samples. In the development of this tool, the Arduino Nano served as the main microcontroller. The Arduino Nano receives data from the load sensor and the tare button to remove the load on the sample container and then processes the data to display the measurement results on the LCD layer. The LED as a balanced indicator when both samples are being weighed. The results of the experiment showed that the developed tool had an average error rate of 1% in the measurement of the weight of the right load cell. Then in the weight measurement of the load cell on the left has an average error rate of 0.3%.